Persistent organochlorine pesticides and cardiometabolic outcomes among middle-aged Latina women in a California agricultural community: The CHAMACOS Maternal Cognition Study - Marcella Warner; Stephen Rauch; Brenda Eskenazi; Lucia Calderon; Robert B. Gunier; Katherine Kogut; Nina Holland; Weihong Guo; Julianna Deardorff; Jacqueline M. Torres (Environment International)
Objective: Environmental exposure to endocrine disrupting compounds is hypothesized to increase risk of cardiovascular disease through effects on obesity, hypertension, dyslipidemia, and insulin resistance. We examined the relationship between serum concentrations of persistent organochlorine pesticides and biologic markers of inflammation and cardiometabolic disease, measured over a decade later, in a cohort of middle-aged and primarily immigrant Latina women living in an underserved agricultural community in California. Material and methods: We used data from the Center for the Health Assessment of Mothers and Children of Salinas-Maternal Cognition Study (CHAMACOS-MCS). We included 468 women who had concentrations of organochlorine pesticides measured in serum collected in 2009–2011 and complete follow-up data in 2022–2024 (blood draw, anthropometry, personal interview). We used Bayesian hierarchical regression models (BHM) to examine the independent effects of five highly correlated pesticides with continuous and binary measures of cardiometabolic disease and inflammation. Results: Participants averaged 49.0 (±5.5) years at follow-up. In BHM models, a 10-fold increase in p,p′-dichlorodiphenyltrichloroethane (DDT) and β-hexacyclohexane (β-HCH) was positively associated with BMI (DDT: adj-β = 1.26, 95 % Credible Interval (CrI): 0.33, 2.20; β-HCH: adj-β = 1.56, 95 %CrI: 0.45, 2.67) and waist circumference (DDT: adj-β = 2.75, 95 %CrI: 0.65, 4.85; β-HCH: adj-β = 3.74, 95 %CrI: 1.24, 6.23). Although credible intervals crossed the null, consistent positive associations were observed for DDT and β-HCH with blood pressure and for DDT with insulin resistance. Trans-nonachlor was positively associated with triglycerides (log-TRIG: adj-β = 0.08, 95 %CrI: 0.02, 0.13). β-HCH was positively associated with inflammatory markers (log-hsCRP: adj-β = 0.11, 95 %CrI: 0.03, 0.19; log-IL-6: adj-β = 0.08, 95 %CrI: 0.03, 0.14). Conclusion: With over a decade of follow-up, we extend evidence on previously reported associations of DDT and β-HCH with several measures of obesity. In addition, we provide new evidence suggesting associations with biomarkers of blood pressure, insulin resistance, dyslipidemia and inflammation, supporting the hypothesis that exposure may have long-term influences on cardiovascular disease risk.